Analisis Pemenuhan Kriteria Sistem Jaminan Halal Pada Pengolahan Lapis Panggang di IKM Rezzen Bakery Malang - Athaya Milda Putri Yuwana; Vira Novia; Adinda Dian Octarina; Refka Mizard Eureksa; Frida Dhia Ramadhani; Amilia Wulandari; Desiana Nuriza Putri (JURNAL AGROINDUSTRI HALAL, 2021)
Based on Law No. 33 of 2014 concerning Halal Product Guarantee, the state is obliged to provide protection and assurance regarding the halalness of products consumed by the public. All food products must include a halal certificate from the Halal Product Guarantee Agency (BPJPH) under the Ministry of Religion (Kemenag). IKM Rezzen Bakery has had a Halal Certificate since 2015 and has made two extensions in 2017 and 2019. Halal. This study aims to analyze the implementation of 11 criteria for the Halal Assurance System (SJH) with the provisions and standards of HAS-23000 at IKM Rezzen Bakery. The importance of implementation analysis is carried out to ensure the halalness of the product during the validity period of the Halal Certificate at IKM Rezzen Bakery. The research method used is descriptive observational. The results showed that Rezzen Bakery had met 10 of the 11 SJH criteria. The ten criteria are halal policy, halal management team, training and education, ingredients, products, production facilities, written procedures for critical activities, traceability, handling of products that are not according to criteria, and management reviews. The internal audit point is not fulfilled because Rezzen Bakeri conducts an internal audit once a year.